In vivo and in vitro antitumor effects of nutrient mixture in murine leukemia cell line P-388 - Roomi, M.W.; Roomi, N.W.; Bhanap, B.; Rath, M.; Niedzwiecki, A. (Experimental Oncology, 2011)
Aim: Leukemia is characterized by uncontrolled marrow cell proliferation and metastatic foci. We investigated the antitumor potential of a nutrient mixture on malignant leukemia P-388 cells. Methods: The nutrient mixture containing lysine, proline, ascorbic acid, green tea extract and other nutrients is formulated to target key pathways in cancer progression. The cells were treated with the mixture, and tested at doses 0, 10, 50, 100, 500 and 1000 μg/ml in triplicates. The effects were evaluated by cell proliferation, Matrigel invasion, cell morphology and apoptosis. The in vivo effect was measured in male nude mice (n = 12) inoculated with P-388 cells. After randomly dividing in two groups, each group was fed regular and the nutrient mixture supplemented diet and the mice were sacrificed after four weeks. Results: The nutrient mixture decreased P-388 cell proliferation at 500 and 1000 μg/ml. Only 10% cells were viable at 1000 μg/ml. Matrigel invasion was significantly inhibited in a dose dependent manner with virtually total inhibition at 1000 μg/ml. Cell morphological features notably changed with dose increase to 1000 μg/ml. Analysis of apoptotic cells on live green caspase kit exhibited gradual increase with the increasing dose of the nutrient mixture, and at 1000 μg/ml 92% of P-388 cells were in late apoptosis. Tumors in the group of mice supplemented with the nutrient mixture had 50% lower weight compared to the tumors in control group (p = 0.0105). Histopathologically, both the groups of tumors were similar, yet size of tumors in the group treated with the nutrient mixture was considerably smaller. Conclusion: These results indicate that the nutrient mixture exhibited significant action against multiple targets in P-388 leukemia and may have potential in human leukemia.